MAKNA FASHION PEMBAWA ACARA PROGRAM KRIBO DI MNC TV (Studi Semiotika Pierce Episode Secangkir Kopi Hitam) - Agung Raharjo (Universitas Bina Sarana Informatika, 2015)
The television show has its own characteristics which give strength and appeal on the television broadcast . One of the teams in the industry is the host of the television program Kribo in MNCTV. As for the meaning of fashion which can be explained from the theory of “semiotics Pierce” as icons , indices and symbols . namely the episode consisted of a cup of black coffee head using frizzy hair wig , clothes worn then use the concept of the 70s . In this study using a qualitative methodology, and then using the critical paradigm and writers critiquing fashion sense emcee Pierce semiotic program Kribo consisting icon, index, and symbols. As defined semiotics Pierce is getting comfort in program Kribo hosted and will be closer to the viewers as well as the speaker , so it looks more formal and there is no restriction or impediment whatsoever to get to know and interact to all sources by wearing the fashion era of the 60 's and 70's in particular in the event program Kribo in MNCTV. Keyword: Fashion, Semiotics, Host, Kribo